A Promise Zone. First Generation of University Students of the National University of La Plata, Argentina (2008–2015) - Martínez, Darío Gabriel (2020)
We propose to reflect on inclusive policies on communication/education implemented in the last years in Argentina. We will work with quantitative data about students admitted to all faculties of the Universidad Nacional de La Plata (UNLP) between 2008-2015. This national university is public, free, and implements unrestricted admission policies. Information was collected from data provided by the Centro Superior para el Procesamiento de la Información (CeSPI, Superior Center for Information Processing) of the UNLP. Two reasons justify the selection of the 2008-2015 period. The first one is linked to Law 26,606 (2006) on compulsory secondary education that came into effect in 2008 at the national level, and in the Buenos Aires province, with the approval of Provincial Education Law No. 13,688 (2007). The second reason relates to the Plan for Primary and Secondary Education Completion (FinES), launched in 2008, as a state initiative to comply with the current legislation about the obligatoriness of the secondary education.